Bending performance of unbonded prestressed basalt fiber recycled concrete beams. (15th October 2020) - Li, Shiping; Zhang, Yibei; Chen, Wujun
Highlights: The flexural tests comprised an elastic stage, a working stage with cracks, and a plastic stage, and the plane-section assumption remains applicable for PRC beams and PBFRC beams. Formulas for calculating flexural bearing capacity and maximum crack width in PRC beams were derived. This lays a theoretical foundation for the application of PRC beams. Formulas for calculating bearing capacity and crack width in PBFRC beams were proposed. This provides a simple and feasible method for calculating bearing capacity and crack width in PBFRC beams. A volumetric basalt fiber dosage of 0.2–0.25% is suggested as optimal for improving the structural strength and safety of recycled concrete structures. Abstract: This study investigated the influences of volumetric basalt fiber dosage and recycled coarse aggregate replacement rate on the flexural performance of unbonded prestressed basalt fiber recycled concrete beams. A symmetric loading test was conducted on nine specimens based on their variety of volumetric basalt fiber dosages and aggregate replacement rates. Failure modes, bearing capacities, deformation characteristics, and crack widths were observed, and the influences of volumetric basalt fiber dosage and recycled coarse aggregate replacement rate on flexural performance are discussed. The bending process of unbonded prestressed recycled concrete beams and unbonded prestressed basalt fiber recycled concrete beams exhibits an elastic stage, a cracking stage, and a failure stage, which is similar to that of conventional unbonded prestressed concrete beams. The addition of basalt fiber can effectively enhance the adhesion between mortar and recycled coarse aggregate, inhibiting crack development, increasing the cracking load, and enhancing ductility. After verifying the applicability of plane-section assumptions via testing, and referring to methods for calculating the bearing capacity of unbonded prestressed conventional concrete beams, formulas for calculating the flexural capacity and maximum crack width of unbonded prestressed recycled concrete beams and unbonded prestressed basalt fiber recycled concrete beams were established. These provide a simple and feasible method for the calculation of flexural capacity and crack width.